Educational management and academic satisfaction in school of infantry school students of the peruvian army. Lima. 2019 - Aguilar Pawelczyk, César Arturo (2020)
Scientific research Institutional Educational Management and its Relationship with the Academic Satisfaction of Student Officers in the Peruvian Army Infantry School, 2019. The general objective is to determine the relationship between the variables Institutional Educational Management and Academic Satisfaction of Student Officers in the Peruvian Army Infantry School, 2019. It is a scientific study with a quantitative, bivariate and cross-sectional approach. With a descriptive - correlational design. The total population is 120 student officers, the sample, through a simple randomization, was made up of 92 student officers. The main result is that; There is a significant relationship between Institutional Educational Management and the Academic Satisfaction of Student Officials. Since: 0.000 <0.05, the researcher's hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. The research concludes that it is shown that there is a strong positive correlation throughout the research, between the variables analyzed and their dimensions.